URBAN CULTURE AND PRIORITY VILLAGE PROGRAMS IN A GLOBAL CONTEXT: CASE STUDY OF KAMPUNG SUSUN BAHARI AKUARIUM - adwani, abdul azis, Mr; Hasan, Chotib (International Review of Humanities Studies, 2023)
Settlement arrangement in Jakarta is refer to the concept of global development context began in the 1900s with the Menteng and New Gondangdia projects at the first. After independence, the expansion of residential land extended to Kebayoran and Tebet, resulting a lesser land for housing development. The existence of kampungs in Jakarta is increasingly shifted by the development of housing complexes. And the impact of increasing urbanization has led to the development of slum areas in Jakarta, thereby putting pressure on the government to provide vertical population services. The DKI Jakarta government then compiled a development strategy to remove slum area in 445 RWs recorded in 2017 through the Priority Kampung development program, one of which was the construction of the Kampung Susun Bahari Akuarium (KSBA) in Penjaringan, North Jakarta. This theme study is a development of an existing study and examines two aspects, namely the aspect of social change in society in terms of urban village culture and changes in occupancy from horizontal housing to vertical housing for people in urban areas with a tropical tropical atmosphere. This study uses a multidisciplinary historical approach by tracing colonial period map documents, mass media news, government policies and past literature searches.